192 Self-reported sleep features in the Italian population across the first and second wave of the COVID-19 pandemic. (3rd May 2021) - De Rosa, Oreste; Cellini, Nicola; Conte, Francesca; Malloggi, Serena; Giganti, Fiorenza; Ficca, Gianluca
Abstract: Introduction: Several studies have shown the negative impact of COVID-19-related confinement measures (spring 2020) on sleep features and quality. Here we aim to follow-up on these data by assessing self-reported sleep characteristics during the second wave of the pandemic (autumn 2020) in Italy, where the government responded with a second, partial, lockdown. Methods: Using a longitudinal approach, 214 participants (Mage=36.78±14.2y; 159F) who had participated in a previous survey (April 2020 – Total Lockdown, TL) completed the same online survey from November 10th to December 1st (Partial Lockdown, PL). In each survey, participants had to respond to a set of questionnaires, including the Pittsburgh Sleep Quality Index (PSQI), referring to their current situation and, retrospectively, to their situation before the lockdown, resulting in four time-points (pre-TL, TL, pre-PL, PL). Results: Linear mixed-model analysis showed that bedtime was delayed from pre-TL (23:46) to TL (24:42) and then linearly advanced in pre-PL (24:02) and PL (23:56). The same pattern emerged for rise time (pre-TL: 07:48, TL: 9:05, pre-PL: 8:28, PL: 7:58) and time in bed, which increased from pre-TL (8h4min) to TL (8h24min) and then linearly decreased (pre-PL: 8h15m, PL: 8h2m). Subjective sleep quality decreased in the two lockdowns compared to the period with no restrictions. The proportion of poor sleepers (PSQI>5) increased from 39.7% (pre-TL) to 48.6% in TL and again from 36.9% (pre-PL) to 47.7% in PL. Conclusion: Sleep habits and quality showed different profiles across four time-points of the COVID-19 pandemic and related restrictive measures. Sleep timing alterations appeared during the first lockdown, recovered after the confinement period, and almost returned to baseline during the second lockdown (likely due to a normalization of working schedules). Instead, subjective sleep quality markedly worsened during both lockdowns relative to the preceding respective months. These data suggest that subjective sleep quality is particularly sensitive to changes in life habits and psychological factors, independently of sleep habits. Considering that the pandemic situation may continue for several months, there is a need for interventions targeting sleep quality. Support (if any): N/A